Case reportEntrapment of the median nerve and the brachial artery by the lacertus fibrosus - Kumar, Hitendra; Das, Srijit; Gaur, Sonali (Archives of Medical Science, 2007)
The lacertus fibrosus is a lesser known cause of high median nerve compression along with the brachial artery. Considering the fact that anatomy literature hardly mentions the lacertus fibrosus, research reports are the only source of information for clinicians and surgeons. The present case report describes in detail the lacertus fibrosus pierced by the median nerve and the brachial artery and discusses its clinical implications, which may be important for clinicians diagnosing nerve entrapment and surgeons operating on the arm